Isoquercitrin Esters with Mono- or Dicarboxylic Acids: Enzymatic Preparation and Properties - Vavříková, Eva; Langschwager, Fanny; Jezova-Kalachova, Lubica; Křenková, Alena; Mikulová, Barbora; Kuzma, Marek; Křen, Vladimír; Valentová, Kateřina (International journal of molecular sciences, 2016)
A series of isoquercitrin (quercetin-3-O-β-d-glucopyranoside) esters with mono- or dicarboxylic acids was designed to modulate hydro- and lipophilicity and biological properties. Esterification of isoquercitrin was accomplished by direct chemoenzymatic reaction using Novozym 435 (lipase from Candida antarctica), which accepted C₅- to C12-dicarboxylic acids; the shorter ones, such as oxalic (C₂), malonic (C₃), succinic (C₄) and maleic (C₄) acids were not substrates of the lipase. Lipophilicity of monocarboxylic acid derivatives, measured as log P, increased with the chain length. Esters with glutaric and adipic acids exhibited hydrophilicity, and the dodecanedioic acid hemiester was more lipophilic. All derivatives were less able to reduce Folin-Ciocalteau reagent (FCR) and scavenge DPPH (1,1-diphenyl-2-picrylhydrazyl) than isoquercitrin; ABTS (2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid)) radical-scavenging activity was comparable. Dodecanoate and palmitate were the least active in FCR and ABTS scavenging; dodecanoate and hemiglutarate were the strongest DPPH scavengers. In contrast, most derivatives were much better inhibitors of microsomal lipoperoxidation than isoquercitrin; butyrate and hexanoate were the most efficient. Anti-lipoperoxidant activity of monocarboxylic derivatives, except acetates, decreased with increasing aliphatic chain. The opposite trend was noted for dicarboxylic acid hemiesters, isoquercitrin hemidodecanedioate being the most active. Overall, IQ butyrate, hexanoate and hemidodecanedioate are the most promising candidates for further studies.
Keywords: kyseliny karboxylové; quercetin; isoquercitrin; fatty acid; katalýza; Quercetin; estery; Antioxidants; log P; Dicarboxylic Acids; Catalysis; DPPH; Proton Magnetic Resonance Spectroscopy; antioxidant activity; lipase; antioxidancia; protonová magnetická rezonanční spektroskopie; Carboxylic Acids; Novozym 435; kyseliny dikarboxylové; molekulární struktura; lipoperoxidation; Esters; Molecular Structure